Calculate the sum of squares for parts (vehicles) SSE in 2n global trials with total integration In a suggested manne - خلف, كمال علوان; محمد, فراس احمد (Journal of Economics and Administrative Sciences, 2009)
In order to serve the field of knowledge in the field of design and analysis of experiments by adopting formulas and methods that are easy and simple in arithmetic work, especially in experiments that require many calculations for squares, including tests of type 2n and total integration, this research aims to contribute to the proposal of how to: Install parameters of processor coefficients when writing a formula for each effect which is one of the requirements for analysis. 2. Calculate the sum of the squares for each part (compound) when the sum of the error squares (SSe) is divided into the 2n type and the total integration of one of the effects of the reactions. In this study, the proposed method, whose contribution to this field was applied, was characterized by simplicity and ease in comparison with the work of the familiar or common formulas used in the calculation of squares.